Processamento e interpretação de linhas sísmicas da região de quebra de talude do Jequitinhonha - CRISTO, Luiz Carlos Ferreira de (2020)
This work aims the implementation of the processing and interpretation of 2D seismic data in the basin Jequitinhonha in slope break region on the continental shelf. This type of seismic data has a large number of multiple surface. A specific seismic processing was applied to the data in order to estimate and eliminate multiple free surface and enhance the seismic data of interest. The interpretation of seismic sections was performed based on the lateral coherence present in each section migrated reflectors are interpreted four (4) to six (6) horizontal surfaces seismic lines, which are sectioned by normal faults, failures roll over, synclines, and possible structural highs present in the basin. Were also observed patterns of prograding seismic terminations, chaotic and onlaps, suggesting that the possible sedimentary layers deposited in this region of the Jequitinhonha Basin have been deposited in environments lamina shallow water with large sediment yield and high energy.